PENGARUH TINGKAT PENURUNAN SALINITAS MEDIA DALAM PROSES AKLIMASI TERHADAP TINGKAT KELANGSUNGAN HIDUP IKAN KERAPU CANTANG (Epinephelus fuscoguttatus - lanceolatus) - Rizal Faozan; M. Bahrus Syakirin; Tri Yusufi Mardiana (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
This study aims to determine the effect of the decrease in media salinity on survival rates of grouper fish and determine the relationship between the survival rate of the cantang grouper and the level of decrease in media salinity in the acclimation process.The study was conducted in June 2018 at the Brackish and Sea Water Laboratory of Pekalongan University in Pekalongan. The test fish used was a cantang grouper with a size of 3-5 cm. This cantang grouper juvenille is obtained from the Situbondo Marine Cultivation Center. The design used was a completely randomized design with 4 treatments and 3 replications. The treatment applied was a decrease in the level of media salinity as follows: 2 ppt/hour, 4 ppt/hour, 6 ppt/hour and 8 ppt/hour. The survival rate of the grouper fish is analyzed using variance analysis. Furthermore, an orthogonal polynomial analysis was performed to correlate the survival rate of the grouper fish to the level of decrease in media salinity.The highest survival rate of the grouper grouper was obtained at a level of decrease in salinity of 2 ppt/hour ie 91.67%, then a decrease in salinity of 4 ppt/hour ie 61.11%, a decrease in salinity of 6 ppt/hour ie 46.67% , and the lowest at a decrease in salinity of 8 ppt/hour which is 25%.The results of the variance analysis revealed that the level of decrease in media salinity had a very significant effect on the survival rate of bushy groupers. The results of orthogonal polynomial analysis showed that the relationship between the survival rate of the grouper fish to the level of decreasing salinity of linear media with the equation: Y = 109.72 - 10.72 X (R2 = 0.97) (R2 = 0.97).